Multi-omics approach to dissect the significance of lipid metabolism in helper T cell subset - Kanno, Toshio; Nakano, Keiko; Iwao, Yukie; Endo, Yusuke (Frontiers in Immunology, 2025)
The immunometabolism has fundamentally reshaped our understanding of T cell biology. Recent advances have demonstrated that metabolic reprogramming is not merely a consequence of T cell activation but a central driver of lineage specification and effector function. For example, quiescent naïve T cells primarily rely on mitochondrial oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO) to meet baseline energy needs, whereas activation triggers a metabolic shift toward anabolic pathways dominated by aerobic glycolysis and de novo biosynthesis of macromolecules. Concurrently, the lipid metabolism confers extensive remodeling: activated T cells upregulate the pathways for de novo fatty acid synthesis and cholesterol biosynthesis, uptake, and storage to sustain membrane biogenesis and signal transduction. Conversely, fatty acid catabolism via β-oxidation is essential for the generation of memory T cells and the differentiation of regulatory T cells. This review reports recent advances by integrating experimental findings and methodological developments, highlighting how metabolic programs across distinct stages of T cell differentiation—with particular emphasis on the lipid metabolism—govern their specialized functions.